VIOLENCIA SEXUAL CONTRA LAS MUJERES EN ESPACIOS PÚBLICOS TURÍSTICOS DEL CANTÓN BABAHOYO - BURGOS CRUZ YUSTHIN YAJAIRA (2024)
The main objective of this research is to determine the incidence of sexual violence against women in public tourism spaces in Babahoyo Canton in order to establish detailed knowledge about the magnitude and frequency of this phenomenon. There is a high probability that women who visit public spaces and develop recreational or tourism activities in Babahoyo have experienced some type of sexual violence, although this phenomenon could be underestimated due to the lack of recognition or shame associated with the subject. The study is based on a descriptive cross-sectional research design with a mixed approach. Two data collection instruments were applied (qualitative and quantitative). A survey was applied to 100 women residents, visitors and tourists in the Babahoyo canton, which collected information on experiences of sexual violence in public tourist spaces. An interview was conducted with the provincial prosecutor in Babahoyo canton to obtain information on the complaints of sexual violence filed with the Prosecutor's Office and the actions being taken to combat this problem. The results of the study reveal that sexual violence against women is a worrying phenomenon in public tourist areas in Babahoyo canton. The women surveyed reported having experienced various types of sexual violence, including verbal harassment, unwanted touching, and sexual aggression.